2020
DOI: 10.1371/journal.ppat.1008235
|View full text |Cite|
|
Sign up to set email alerts
|

Pervasive within-host recombination and epistasis as major determinants of the molecular evolution of the foot-and-mouth disease virus capsid

Abstract: Although recombination is known to occur in foot-and-mouth disease virus (FMDV), it is considered only a minor determinant of virus sequence diversity. Analysis at phylogenetic scales shows inter-serotypic recombination events are rare, whereby recombination occurs almost exclusively in non-structural proteins. In this study we have estimated recombination rates within a natural host in an experimental setting. African buffaloes were inoculated with a SAT-1 FMDV strain containing two major viral sub-population… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
5
13
0
Order By: Relevance
“…These hotspots separated the ORF into three distinct regions, corresponding well to the established functional areas 6 . This suggested that recombination in FMDV is constrained by biological functions, and further supported the idea of mosaic structure of FMDV genome 17 19 . The genome of other viruses has also been observed to have a mosaic and modular nature, such as foamy virus 31 , and enteroviruses 32 , for example.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…These hotspots separated the ORF into three distinct regions, corresponding well to the established functional areas 6 . This suggested that recombination in FMDV is constrained by biological functions, and further supported the idea of mosaic structure of FMDV genome 17 19 . The genome of other viruses has also been observed to have a mosaic and modular nature, such as foamy virus 31 , and enteroviruses 32 , for example.…”
Section: Resultssupporting
confidence: 64%
“…The third region mapped to the P2 and P3 regions (nt 3,034–6,840; P2–3 alignment), excluding the 2A coding region. As previously noted, only a few recombination events were detected in the P1 region, which codes for capsid protein subunits 15 19 . A previous study of serotype O, A, and Asia‐1 FMDVs circulating in West Eurasia also showed that, while the VP1–3 phylogenies were the same, a phylogeny estimated from the VP4 coding region was different from the rest 33 .…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Recombination occurred at a high rate during the acute phase of infection postinoculation and at a lower rate during the persistent phase, as discussed in detail in a companion publication by Ferretti and colleagues (28).…”
Section: Resultsmentioning
confidence: 90%